The Ego Phenomenon and the Doping Problem in Sport: A Historical Conceptual Analysis - Steyn, Barend J. M.; Nolte, Kim (Frontiers in Sports and Active Living, 2021)
The concept of ego has various meanings in the field of Psychology, depending on the paradigmatic and theoretical framework point of departure. The ego phenomenon as operationalized and measured in the theoretical framework of goal orientation will be the contextual framework for a historical conceptual analysis. In the last three decades, research in the theoretical framework of goal orientation has revealed a positive relationship between ego involvement and the tendency to use prohibited substances to enhance performance in sport. The concept of the ego phenomenon as operationalized within goal orientation theory and meanings attached to the concept can be connected to historic oriental writings that were written approximately 2500 years ago. These attached meanings to the ego phenomenon include elements of extreme competitiveness and outcome orientation, as well as social comparison and the external norm for the measurement of success and failure. These meanings can be traced back to classical works involving the Bhagavad Gita, the Tao Te Ching and the Eastern Origins of Mindfulness that are part of the broader Buddhist philosophical system. Meister Eckhart, a 12th Century German theologian, in his significant contribution on the analysis of the having mode as opposed to the being mode also provides insight into the ego phenomenon that can explain why the ego phenomenon can be linked to some of the deeper psychological motives of using prohibited substances. Researchers in Psychology do not yet have a full understanding of why certain athletes dope or have a susceptibility to use prohibited substances or performance enhancing drugs (PEDs) and thus the motivation for this historical conceptual analysis of the ego phenomenon. Therefore, the aim of this article is to deepen the understanding of psychological motives of athletes who exhibit tendencies toward cheating in general and the proclivity to use prohibited substances.